PREDICTORS OF PHYSICAL ACTIVITY AMONG CZECH AND AMERICAN CHILDREN WITH HEARING IMPAIRMENT - Martin, J. Jeffrey; Shapiro, R. Deborah; Prokesova, Eva (European Journal of Adapted Physical Activity, 2013)
Research is scarce in relation to using social-cognitive theory inclusive of social-cognitive, affective and environmental constructs to predict physical activity (PA) and fitness with hearing impaired (HI) children. Hence, the purpose of our investigation was to evaluate the ability of social cognitive variables (e.g., self-efficacy and social support), environmental (i.e., time outside) and affective constructs (e.g., physical activity enjoyment) to predict PA. Children from the Czech Republic and the USA (N = 64, M age = 14.1) with hearing impairments completed questionnaires assessing predictor variables and PA. Using multiple regression analyses we accounted for 29% of the variance in PA. Based on standardized beta-weights, the best predictors of PA were gender, country, and a block of social-cognitive constructs. Compared to males and females from the Czech Republic and to females in the USA, American males receiving social support from their friends and who enjoyed physical education were the children most likely to be physically active. Future research examining environmental influences more fully (e.g., school settings, after school programs) both within the USA and cross-culturally and adult influences beyond parents (e.g., teachers, coaches) are encouraged.
Keywords: social cognitive theory; environmental influences; adapted physical activity